Popular Influenza Antiviral Drugs: Mechanisms, Efficacy, and Resistance - Ley, Sidney (BioScientific Review, 2023)
Influenza viruses cause acute respiratory infections responsible for significant mortality and morbidity around the world. Various factors, such as antigenic drift, allow influenza strains to avoid being fully suppressed by seasonal vaccines. This has led to the increased scrutiny of antivirals as treatment and prophylaxis options for seasonal outbreaks and potential pandemics. Unfortunately, many influenza antivirals suffer from a lack of adequate clinical trials, as well as a lack of toxicity data. This is especially true of umifenovir (arbidol), a drug popularly used for the prevention and treatment of influenza strains in China and Russia. Neuraminidase inhibitors, though widely prescribed, display a potential for future resistance. Adamantanes, while proven to be effective in treating influenza A, are already encountering rapid and widespread cross-resistance and are effectively obsolete. Baloxavir marboxil, a newer antiviral, shows promise in treating acute uncomplicated influenza and may avoid the development of resistance when co-administered with other antiviral drugs. Indeed, the low genetic barrier to resistance associated with influenza antivirals could potentially be overcome by co-administration with other antivirals. This review explores the most widely prescribed antivirals for influenza treatment, their mechanisms of action, and the data currently available about their susceptibility to resistance and efficacy.